Critical-Size Calvarial Bone Defects Healing in a Mouse Model with Silk Scaffolds and SATB2- Modified iPSCs - Ye, Jin-Hai (2011)
Induced pluripotent stem cells (iPSCs) can differentiate into mineralizing cells and thus have a great potential in application in engineered bone substitutes with bioactive scaffolds in regeneration medicine. In the current study we characterized and demonstrated the pluripotency and osteogenic differentiation of mouse iPSCs. To enhance the osteogenic differentiation of iPSCs, we then transduced the iPSCs with the potent transcription factor, nuclear matrix protein SATB2. We observed that in SATB2-overexpressing iPSCs there were increased mineral nodule formation and elevated mRNA levels of key osteogenic genes, osterix (OSX), Runx2, bone sialoprotein (BSP) and osteocalcin (OCN). Moreover, the mRNA levels of HoxA2 was reduced after SATB2 overexpression in iPSCs. The SATB2-overexpressing iPSCs were then combined with silk scaffolds and transplanted into critical-size calvarial bone defects created in nude mice. Five weeks post-surgery, radiological and micro-CT analysis revealed enhanced new bone formation in calvarial defects in SATB2 group. Histological analysis also showed increased new bone formation and mineralization in the SATB2 group. In conclusion, the results demonstrate that SATB2 facilitates the differentiation of iPSCs towards osteoblast-lineage cells by repressing HoxA2 and augmenting the functions of the osteoblast determinants Runx2, BSP and OCN.